2020
DOI: 10.1111/1467-9566.13075
|View full text |Cite
|
Sign up to set email alerts
|

Understanding self‐construction of health among the slum dwellers of India: a culture‐centred approach

Abstract: Disembarking from a traditional approach of narrow hazardous environmental and structural conditions in understanding urban slums' health problems and moving towards a new notion of what constitutes health for slum dwellers will open a new avenue to recognise whether and how health is being prioritised in disadvantaged settings. Drawing on in-depth semi-structured interviews with a total of 67 men and 68 women from Kolkata slums and 62 men and 48 women from Bangalore slums, this study explored how knowledge, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Despite their efforts to optimise their resources, the data indicates that they are experiencing a gradual contraction in their social and economic horizons. As a result, as previously demonstrated in other studies (Das et al, 2020), Kolkata Slums respondents commonly consult traditional healers who are connected with their traditional culture and meet their culturally mediated emotional expectations. Additionally, as found in earlier studies, remaining loyal to traditional healthcare is connected to more structural and normative limitations than other social bonds, resulting in patients becoming less malleable and changeable (Blieszner, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…Despite their efforts to optimise their resources, the data indicates that they are experiencing a gradual contraction in their social and economic horizons. As a result, as previously demonstrated in other studies (Das et al, 2020), Kolkata Slums respondents commonly consult traditional healers who are connected with their traditional culture and meet their culturally mediated emotional expectations. Additionally, as found in earlier studies, remaining loyal to traditional healthcare is connected to more structural and normative limitations than other social bonds, resulting in patients becoming less malleable and changeable (Blieszner, 2014).…”
Section: Discussionsupporting
confidence: 56%
“…The outbreak of COVID-19, the associated lockdown and disruptions in global supply chains had accentuated the slowdown of the global economy, while the failure to provide a social security net in developing countries like India had created economic insecurity [29]. These circumstances may be expected to increase the incidence of mental health problems, particularly among vulnerable sections [6,54].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Misra et al amongst elderly participants living in urban slums indicated 50% of people were having knowledge about cataracts, related symptoms, and treatment options, and the knowledge was positively associated with years of schooling, and employment [ 18 ]. Males were more likely to present with knowledge about cataracts compared to women.…”
Section: Reviewmentioning
confidence: 99%